Richard Stoneman, Ursula Sims-Williams, Adrian S. Edwards and Peter Toth (eds) Alexander the Great: the Making of a Myth. - Erskine , Andrew (Journal of Greek Archaeology, 2024)
The reign of the Macedonian king Alexander III is marked by destruction: razing Thebes to the ground, the overthrow of the Persian empire, the burning of Persepolis, the murder and execution of his associates (Clitus, Parmenio, Callisthenes, etc.), and the killing of countless others who remain unnamed and unknown. Seven years after his final victory over the Persian king Darius, he was dead with no heir capable of taking his place. In his famous and no doubt apocryphal last words he envisaged the wars for his empire as his funeral games. The legacy of this short and violent reign was the establishment of Greco-Macedonian political and cultural dominance in the Eastern Mediterranean, albeit not as a unified Macedonian empire, but rather as a group of kingdoms ruled by rival Macedonian warlords. In spite of this, Alexander has emerged as one of the most well-known and heroic figures from antiquity.